Natural Fiber Composites from Coconut Fiber, Wood Powder, and Shellfish Shell of Centrifugal Clutch Materials - Ahmad Kholil; Riyadi Riyadi; Siska Titik Dwiyati; Eko Arif Syaefuddin; Randika Hadi Pratama; Yuda Dwi Rama Putra (Universitas Muhammadiyah Magelang, 2022)
Natural fiber materials are the sustainable sources used for future automotive elements, where the centrifugal clutch utilizes the frictional force on the clutch pads to transfer kinetic energy from the rotating crankshaft to the transmission and the wheels. These pads are produced from several natural composites, such as coconut fiber, as well as wood and shellfish powder, whose characteristics are being investigated for hardness, microstructure, and wear properties. Based on this study, performance analysis was carried out on the samples of composite centrifugal clutch applied to automatic motorcycles. As a comparison, subsequent analysis was conducted on the genuine clutch pad materials, where the results showed differences in the characteristics of each mixture composition of the natural fiber composites. This indicated that the addition of wood powder composition to the clutch pad increased the hardness and special wear values by an average of approximately 12.9 and 1.16%, respectively. Furthermore, the composite content was observed in the microstructure, as the maximum power and torque on the natural fiber materials were 10.7 hp and 17.17 N.m, respectively. The value was found to be closely similar to the genuine parts with maximum power and torque of 10.8 hp and 16.02 N.m, respectively.